Isoform-Specific Role of Akt Kinase in Cancer and its Selective Targeting by Potential Anticancer Natural Agents - Roy, Nand K.; Monisha, Javadi; Singh, Anuj Kumar; Padmavathi, Ganesan; Kunnumakkara, Ajaikumar B. (Natural Products Journal, The, 2020)
Background: Akt kinase is a serine/threonine kinase that plays an important role in different cellular processes such as cell proliferation, apoptosis, glucose metabolism, transcription, and cell migration. It has three isoforms (Akt1, 2, and 3) that have distinct and sometimes contrasting functions in different cancers. However, to date, most of the inhibitors are directed against Akt kinase generally which would not serve the purpose due to the lack of isoform selectivity and offtarget toxicity. Therefore, the present study is an elementary step towards the demarcation of the natural inhibitors available from food sources and dietary supplements using in silico methods. Objective: To demarcate the natural agents and general Akt kinase inhibitors into Akt isoformspecific inhibitors. Methods: The genetic alterations data for Akt isoforms were obtained from The Cancer Genome Atlas datasets. The protein sequence alignment was achieved using PRALINE program. The modeling of Akt3 protein and its evaluation was performed by ModWeb Server and PROCHECK program, respectively. The docking was performed by using Schrödinger Glide software. Results: Differential pattern of genetic alterations of Akt isoforms was observed in different cancers. The protein sequence alignment has shown both the conserved as well as the non- conserved region of Akt isoforms. The structure of Akt3 was successfully modeled and evaluated. Finally, with the help of molecular docking, the natural agents and general Akt inhibitors have been segregated into Akt isoform-specific inhibitors based on the derived Glide Score (GScore). Conclusion: Isoform-specific inhibition of Akt would have huge clinical significance and research should be commenced in preclinical and clinical settings.
Keywords: Natural agents